Peningkatan Budaya Literasi Anak di Taman Kanak-Kanak Nurul Fikri Bekasi Utara - Ayuningtyas, Fadilla; Wijayanti, Ellita Permata (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2019)
In this millennial era our society’s ability to read is increasingly eroded by the presence of technology. Gadget is not only enjoyed by adults, but also by children even from an early age. At TK Nurul Fikri, Alamanda Regency Housing in North Bekasi, 100% of parents said that they gave a gadget to their children. Mothers also have a relatively low level of education. The Community Empowerment Program is carried out through an awareness method by providing material and training related to child care in the digital era. This program involves speakers and trainers who have been involved in parenting world. The storytelling training programs, which was carried out to improve maternal skills in educating children, are also supported by training in making story-telling materials from used goods. Through the skill playing method, children are also stimulated to be closer to literacy culture. Through this program, mothers become more open-minded and trained to build their children literacy culture. Thus children are expected to get more positive values ​​from their close environment.